The question is x^2dy/dx + y^2=0 , y(1)=3(adsbygoogle = window.adsbygoogle || []).push({});

I re-arrange the equation to get -1/y^2dy=1/x^2dx

Seperated them, then I integrate both sides to get 1/y=-1/x + c

Now I dont get how they got the answer y=3x/(4x-3), as when I try use the condition I get a different answer, could anyone help? I might have done something wrong in the integration?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# First order ODE with condition

**Physics Forums | Science Articles, Homework Help, Discussion**